COAGULATION ACTIVITY AND D-DIMER IN SEPSIS PATIENTS - Anggraini D; Maani H; Rofinda Z D (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Sepsis is a systemic inflammatory response with the presence of suspected or proven infection. The inflammation will increase the production of proinflammatory cytokines that will activate coagulation and suppress fibrinolytic system. An imbalance of hemostasis mechanism and inflammation in sepsis can progress into Disseminated Intravascular Coagulation (DIC). The objective of this study was to determine the coagulation activity (platelet count, Prothrombin Time (PT), activated Partial Thromboplastin Time (aPTT)), and D-dimer in sepsis patients. A descriptive study was conducted at the Dr. M. Djamil Hospital on December 2012-July 2013. Subjects were adult patients with two or more of four criteria for Systemic Inflammatory Response Syndrome (SIRS) and presence of suspected or proven infection admitted to the Department of Internal Medicine. Laboratory examination was conducted in the Clinical Pathology Laboratory Dr. M. Djamil Hospital including the coagulation activity and D-dimer level. Data were processed manually and presented in distribution tables, and diagrams. Subjects of this study were 54 sepsis patients, consisting of 57% males and 43% females with a median age of 53.5 year-old, platelet count 188.5 x 103/µL, PT 13.7 seconds, aPTT 39.3 seconds, and D-dimer level 1.15 μg/mL. Based on this research it can be concluded that coagulation activity in sepsis patients showed that platelets count were still in the normal range while PT and aPTT were prolonged and D-dimer levels were increased.